1987
DOI: 10.2307/1130551
|View full text |Cite
|
Sign up to set email alerts
|

Hormones, Emotional Dispositions, and Aggressive Attributes in Young Adolescents

Abstract: Relations among hormone levels, emotional dispositions, and aggressive attributes were examined in 56 boys and 52 girls, age 9 to 14 years. The adolescents represented all 5 stages of pubertal development. Serum levels of gonadotropins, gonadal steroids, adrenal androgens, and testosterone-estradiol binding globulin were assessed. Levels of these hormones were related to stage of pubertal development and were assumed to represent relatively stable biological characteristics. The emotional dispositions assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
2

Year Published

1987
1987
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(110 citation statements)
references
References 48 publications
(74 reference statements)
6
99
1
2
Order By: Relevance
“…Although aggressive behavior is related to neurobiological factors, links between hormones and externalizing behavior in adolescents remain ambiguous, with much of the research and significant results obtained only for boys. For example, there appears to be a weak association between aggression and higher circulating testosterone (Book et al, 2001), higher levels of LH, and lower levels of FSH levels in boys (Susman et al, 1987). Results have not been replicated in girls, and -in the case of FSH, which is higher in early maturers -contradict an expected association.…”
Section: Delinquencymentioning
confidence: 92%
“…Although aggressive behavior is related to neurobiological factors, links between hormones and externalizing behavior in adolescents remain ambiguous, with much of the research and significant results obtained only for boys. For example, there appears to be a weak association between aggression and higher circulating testosterone (Book et al, 2001), higher levels of LH, and lower levels of FSH levels in boys (Susman et al, 1987). Results have not been replicated in girls, and -in the case of FSH, which is higher in early maturers -contradict an expected association.…”
Section: Delinquencymentioning
confidence: 92%
“…Likewise, in initial work with human adolescents, few reliable relationships were observed between gonadal hormones and adolescent brain function [362] or behavior, the latter prompting Susman and colleagues [530] to assert: "at a folk-wisdom level, hormonal changes are associated with behavior change in adolescents. The empirical evidence confirming this link is almost nonexistent."…”
Section: How Closely Are These Hormonal Alterations Associated With Bmentioning
confidence: 99%
“…Evolutionary psychologists have shown that sex differences in many traits related to reproduction increase as individuals approach maturity, which is potentially adaptive in attracting mates (Geary, 1998). Moreover, pubertal timing and associated changes in hormone levels during adolescence are related to sex-typed attributes, including aggression and social dominance (Schaal, Tremblay, Soussignan, & Susman, 1996;Susman et al, 1987; for a review, see Geary, 1998), as well as emotional distress (Brooks-Gunn, Graber, & Paikoff, 1994;Susman, Dorn, & Chrousos, 1991). Social influences may have unique effects on sex-typed processes or may augment sex differences elicited by biological factors.…”
Section: A Developmental Perspectivementioning
confidence: 99%